LOKSAMGRAH: AN AFFIRMATIVE THOUGHT FOR SOCIAL RECONSTRUCTION - Bishoyi, Jatin (International Journal of Research -GRANTHAALAYAH, 2017)
For Bhagavad-Gita, both individual and society as a whole is dependent on three principal conditions for their existence such as Niskama karma, Svadharma and Loksamgrah. Loksamgrah is used in a very comprehensive connotation as it not only looks at the collective well-being of this world but the universe as a whole. It is because in Loksamgrah the word ‘Loko’ does not mean only people of this world but all the beings of satyaloka, pitruloka, devaloka, bhurloka and other loka. In Gitarahasya Tilak points out, “The word ‘Loksamgrah’ has been used in the Bhagavad-Gita to mean the maintenance, not only of human beings, but that the human and all others spheres, such as of the Gods etc. should be maintained, and that they should become mutually beneficial”. True to say the recommendation of Loksamgrah on our public life have triggered concerns that public services, ranging from physical world to metaphysical world could become more imperative but in fact, it only would have minimal impact on public life i.e. it only attempts to minimize distress and problems both at individual and society levels. As a whole it could only attempt to inculcate the values of public service and integrity attitude. Radhakrishnan points out that, “Loksamgrah stands for the unity of the world, the interconnectedness of society. If the world is not to sink into a condition of physical misery and moral degradation, if the common life is to be decent and dignified, religious ethics must control social action”.